Comparison of outcomes of the patients with acute cholecystitis treated in the COVID-19 pandemic and pre-pandemic period - Lapsekili,Emin (2021)
SUMMARY OBJECTIVE: The coronavirus disease 2019 (COVID-19) pandemic has affected the health care system in an unpredictable way. In this study, we aimed to analyze the effects of the pandemic process on the disease severity on admission, management strategies, and outcomes of patients. METHODS: The medical records of the patients who applied to the emergency department and consulted to the general surgery clinic from March 2020 until January 2021 were retrospectively reviewed as the pandemic period. For the control group, patients’ medical records in the same time interval of 2019 were evaluated as the pre-pandemic period. RESULTS: A total of 88 patients in the pre-pandemic period and 89 patients in the pandemic period were treated for acute cholecystitis. There was no statistically significant difference between the two groups in terms of the treatment strategies and length of hospital stay between the two periods (p=0.087 and p=0.587, respectively). CONCLUSIONS: In the pandemic period, it is thought that postponing and bridging treatments may replace surgery for reducing the risk of contamination of both patients and health care workers.